Employing target costing technology under the adoption of cleaner production to reduce cost: المحاسبة والتقرير عن خطط منافع التقاعد (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to reduce costs by applying cleaner production technology in the Kufa Cement Plant to reach the target cost by working to improve production processes, which helps increase production efficiency and operate the plant with its full available capacity, which helps meet the needs of customers and achieve a larger market share for the plant. The researcher relied on analyzing data and information obtained through field visits to the factory and reviewing records of costs and production prepared by the relevant departments in the factory, as well as through questions, inquiries and interviews with the employees working in the factory and the engineers responsible for the production process in the factory.A set of conclusions were reached, the most important of which are: The application of cleaner production in the factory led to improving production processes and increasing production efficiency. The application of cleaner production also helped reduce production costs and reach the target cost. Therefore, the application of cleaner production helps the factory meet customer demands and achieve market share. The factory is larger, and cleaner production has helped increase the production capacity available in the factory.